Essentials of WMS-IV assessment - Drozdick, Lisa Whipple (Essentials of psychological assessment series, 2011)
Integrating WMS®-IV data with the WAIS®-IV and other measures of cognitive ability and memory for adults, Essentials of WMS®-IV Assessment now includes four new subtests and a revised index structure. The authors also offer expert assessment of the test's relative strengths and weaknesses, valuable advice on its clinical applications, and several illuminating case studies. --Book Jacket.